Deuterium oxide validation of bioimpedance total body water estimates in Hispanic adults - Tinsley, Grant M.; Park, Kyung-Shin; Saenz, Catherine; Mehra, Ayush; Esco, Michael R.; Czerwinski, Stefan A.; Nickerson, Brett S. (Frontiers in Nutrition, 2023)
Background: To date, body composition assessments in Hispanics, computed via bioimpedance devices, have primarily focused on body fat percent, fat mass, and fat-free mass instead of total body water (TBW). Additionally, virtually no information is available on which type of bioimpedance device is preferred for TBW assessments in Hispanic populations. Purpose: The purpose of this study was to validate two bioimpedance devices for the estimate of TBW in Hispanics adults when using a criterion deuterium oxide (D2O) technique. Methods: Onehundred thirty individuals (males: n=70; females: n=60) of Hispanic descent had TBW estimated via D2O, single-frequency bioimpedance analysis ([SF-BIA] Quantum V, RJL Systems) and bioimpedance spectroscopy ([BIS] SFB7 Impedimed). Results: The mean values for SF-BIA were significantly lower than D2O when evaluating the entire sample (37.4L and 38.2L, respectively; p<0.05). In contrast, TBW values were not statistically significant when comparing D2O against BIS (38.4L, p>0.05). Bland-Altman analysis indicated no proportional bias when evaluating the entire sample for SF-BIA or BIS. The standard error of estimate and total error values were ≤ 2.3L and Lin's concordance correlation coefficient were ≥0.96 for all comparisons. Conclusion: The SF-BIA and BIS devices evaluated in the current study hold promise for accurate estimation of TBW in Hispanic adults. While both methods demonstrated relatively low errors relative to the D2O criterion, BIS exhibited a more consistent performance, particularly at the group level. These findings provide essential information for researchers and clinical nutrition practitioners assessing TBW in Hispanic adults.